Intellectual Property Protection Flexibility and Food Security in Indonesia: Towards an Inclusive Innovation Framework - Kanti Rahayu; Kus Rizkianto; Youssef Baqil (Universitas Muhammadiyah Purwokerto, 2026)
This study examines the urgency of flexible intellectual property (IP) protection policies in supporting food security in Indonesia. The research employs a normative juridical approach combined with library research by analyzing legal regulations, international agreements, and academic literature related to intellectual property protection, agricultural innovation, and access to genetic resources. The findings reveal that Indonesia’s current IP protection framework, particularly in patents, plant variety protection, and biotechnology, faces challenges in balancing exclusive rights with public interests. A rigid IP regime may limit farmers’ access to seeds, agricultural technologies, and genetic resources, potentially affecting food sovereignty and national food security. This study demonstrates that policy flexibility is essential to harmonize innovation incentives with farmers’ rights and public access. Such flexibility can be achieved through compulsory licensing, research and public interest exceptions, sui generis plant variety protection, and recognition of traditional knowledge and genetic resources. The study contributes to the development of an IP policy framework that integrates innovation protection with social justice and sustainable food security objectives. Reformulating Indonesia’s IP policies toward a more flexible approach is necessary to ensure equitable access to agricultural technologies while promoting inclusive and sustainable food security.